Harga dan Kualitas Produk terhadap Keputusan Pembelian Mobil yang Dimediasi Kepuasan Konsumen - Lionarto Lionarto; Melitina Tecoalu; Soegeng Wahyoedi (Journal of Management and Bussines (JOMB), 2022)
This study aims to determine the effect of price and product quality on car buying decisions mediated by consumer satisfaction. This research method is quantitative research with 100 respondents spread across DKI Jakarta. Data processing using SMARTPLS 3.3 data processing. The results showed that the results of the T test were, a) the price variable on consumer satisfaction had a statistical t value of 1.052 < 1.96 and p-value 0.294 > 0.05; b) product quality variable on consumer satisfaction has a statistical t value of 6.457 > 1.96 and p-value 0.000 < 0.05; c) the price variable on consumer purchasing decisions has a t-statistic value of 2.698 > 1.96 and a p-value of 0.007 < 0.05; d) the product quality variable on consumer purchasing decisions has a t-statistical value of 2.796 > 1.96 and p-value 0.005 < 0.05; e) the variable of consumer satisfaction with purchasing decisions has a t-statistical value of 3.471 > 1.96 and a p-value of 0.001 < 0.05; f) the price variable on purchasing decisions with consumer satisfaction as a mediating variable has a statistical t value of 1.051 < 1.96 and p-value 0.294 > 0.05; g) the experiential marketing variable on repurchase intention with consumer satisfaction as a mediating variable has a statistical t-value of 2.669 > 1.96 and a p-value of 0.008 < 0.05. In conclusion, there are two variables that have no significant effect, namely the price variable on consumer satisfaction and the price variable on consumer decisions mediated by consumer satisfaction. While other variables have a significant effect, namely, a) product quality on consumer satisfaction; b) prices on consumer purchasing decisions; c) product quality on consumer purchasing decisions; d) consumer satisfaction with purchasing decisions; e) experiential marketing on repurchase intention with consumer satisfaction as a mediating variable. Keywords: Price, Consumer Satisfaction, Purchase Decision, Product Quality